THE EFFECT OF USE DIFFERENT LEVEL BUFFALOS FERMENTED COMPOST ON THE PRODUCTIVITY AND QUALITY OF GRASS (PASPALUM CONJUGATUM, BRACHIARIA DECUMBENS, DIGITARIA MILANJIANA) - Prawestri Dwi P; T H Wahyuni; N D Hanafi; E Mirwandhono; N Ginting (Jurnal Peternakan Integratif, 2017)
Abstract.There seach objective was to determine the productivity and nutrient content of Paspalumconjugatum, Brachiariadecumbens, Digitariamilanjiana by buffalo fermented compost. The research was conducted at the Goat Farm Research Station SeiPutih, SubdistrictGalang, LubukPakam, North Sumatra from October 2015 through February 2016. The design used was split plot design (plots divided) with mainplotwas kind of grass A1 (Paspalumconjugatum), A2 (Brachiariadecumbens), A3 (Digitariamilanjiana) and the subplot was fertilizer dose as the level (0, 10, 20 and 30 t/ha/y). The parameters studied were production of fresh, high plant, number of tillers, dry matter, crude protein, and crude fiber. The results showed that administration of buffalo fermented compost better than without the use of fertilizers. Dosing compost  significant affect (P<0.05) in increasing production of fresh, high plant, number of tillers, dry matter, crude protein and crude fiber. The conclusion of this study that the  best dose was 30 t/ha/y of  buffalo fermented compost  and the best interactions was dose of 30 ton/ha/year on Digitariamilanjiana. Keywords: Paspalumconjugatum, Brachiariadecumbens, Digitariamilanjiana, buffalo fermented compost, dose, kind of grass